The Relationship Between Individual Characteristics and Family Support with Adherence to a Low-Salt Diet Among Hypertensive Patients at Teluk Pucung Public Health Center Bekasi City in 2025 - Nurhanifah, Nasya Alif; Birwin, Alib; Mardhiati, Retno (Universitas Veteran Bangun Nusantara, 2025)
Background: Hypertension is a non-communicable disease whose cases are increasingly being found in Indonesia. Adherence to a low-sodium diet plays a crucial role in controlling blood pressure among individuals with hypertension. This study aimed to examine the relationship between individual characteristics and family support with adherence to a low-salt diet among hypertensive patients at the Teluk Pucung Public Health Center, Bekasi City. Method : This study employed a quantitative approach with a cross-sectional design. A total of 80 participants were selected using a purposive sampling technique. Primary data were collected through interviews using a questionnaire and analyzed using univariate and bivariate analyses with the Chi-Square test. The results showed that 59 out of 80 respondents (73.8%) adhered to a low-salt diet. Most respondents are elderly (53,8%), female (67.5%), had a high education level (78.8%), were unemployed (73.8%), suffering hypertension of short duration (67.5%), and received good family support (51.2%). Bivariate analysis indicated a significant association between adherence to a low-salt diet and the variables of gender and family support (p < 0.05), whereas age, education, occupation, and duration of hypertension were not significantly associated (p > 0.05). Conclution :This study shows that most hypertensive patients at the Teluk Pucung Public Health Center adhered to a low-salt diet. Therefore, community health centers are expected to actively involve family members as part of the strategy to improve patients' adherence to a low-sodium diet. Keywords: Adherence, Diet, Family, Hypertension, Salt